Evolution of Nuclear Shapes and Structure in Tellurium, Xenon, Barium and Cerium Isotopes - Abolghasem, M.; Alexa, P.; Repko, A.; Reinhard, Paul-Gerhard (Acta Physica Polonica B, 2019)
Different Skyrme functional parametrizations were tested for Te, Xe, Ba and Ce isotopes for N > 82. For the SVsym34 parametrization, which best fits the experimental binding energy, potential energy curves obtained from constrained beta(2), beta(3) and beta(4) Hartree-Fock+BCS calculations were investigated. Positions of the lowest quadrupole and octupole vibrational states and the lowest 2(+) rotational states in deformed nuclei were obtained within the Skyrme QRPA and compared to existing experimental data.
CRIS-Team WoS Importer:2019-04-23